2014
DOI: 10.1182/blood-2014-01-552067
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation as a mechanism of Wnt/β-catenin pathway activation in CLL

Abstract: Key Points Wnt pathway is frequently mutated in CLL. Wnt pathway mutations can lead to pathway activation and enhanced CLL survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 37 publications
(64 reference statements)
1
56
0
Order By: Relevance
“…The functional role of several putative driver mutations has been confirmed; for example, silencing mutated WNT pathway genes in primary CLL cells resulted in decreased cell viability 47 . Mutations in POT1 , which has a role in the protection of telomeres, prevented the binding of protection of telomeres protein 1 to telomeric DNA, resulting in numerous chromosomal abnormalities, in addition to the development of abnormal telomeres.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 96%
“…The functional role of several putative driver mutations has been confirmed; for example, silencing mutated WNT pathway genes in primary CLL cells resulted in decreased cell viability 47 . Mutations in POT1 , which has a role in the protection of telomeres, prevented the binding of protection of telomeres protein 1 to telomeric DNA, resulting in numerous chromosomal abnormalities, in addition to the development of abnormal telomeres.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 96%
“…Analysis of an independent DLBCL cohort from The Cancer Genome Atlas confirmed that 78% of individual DLBCL samples had upregulated mRNA expression of genes from IEGS. The analysis of additional cohorts from other cancers evidenced an individual variation of IEGS expression among patients with chronic lymphocytic leukemia (CLL) (NCBI GEO data set GSE31048 32 ), and no significant upregulation of the IEGS in samples from multiple myeloma patients (NCBI GEO dataset GSE6691 33 ) (Fig. 1F).…”
Section: Fl and Dlbcl Upregulate The Expression Of Immune Escape Genesmentioning
confidence: 99%
“…1E), the random distribution of ECDF of IEGS was tested by one-sample KS test. The same procedure was applied to other samples of NHL 30 : ABC and GC samples of DLBCL from the study GSE12195, 29 MM samples of the study GSE6691 33 and CLL samples of the study GSE31048 32 (ECDFs shown in red, Fig. 1F).…”
Section: Ks Tests For Iegs Distribution Analysismentioning
confidence: 99%
“…[24] The canonical Wnt pathway controls intracellular levels of β-catenin, a protein independently involved in cell adhesion and co-transcriptional activity for Wnt signal transduction [25,26] Dysregulation of the Wnt pathway has been heavily implicated in multiple human diseases, especially in cancers such as colorectal cancer, [27] chronic lymphocyte leukemia [28], gastric cancer [29], hepatocellular cancer [30], prostate cancer [24, 31], and breast cancer [24,31]. In ovarian cancer, activation of the Wnt pathway plays an important role in ovarian cancer chemoresistance to drugs such as cisplatin.…”
Section: Discussionmentioning
confidence: 99%